THE INFLUENCE OF FINANCIAL LITERACY AND RELIGIOSITY ON THE CONSUMPTIVE BEHAVIOR OF SHARIA ECONOMICS STUDENTS OF KERINCI STATE ISLAMIC INSTITUTE - Anggraini, Selia; Syarif, Dafiar; Bustami, Bustami (Asian Journal of Islamic Economic Studies, 2024)
This research aims to determine the influence of literacy and religiosity on the consumptive behavior of sharia economics students. The type of research used is quantitative research. The sample used a random sampling technique with a sample size of 80 people. Testing uses Multiple Linear Regression Analysis. The results show that financial literacy has a significant influence on consumer behavior. Religiosity has a significant influence on consumer behavior. Financial literacy and religiosity have a simultaneous influence on the consumptive behavior variable of sharia economics students at IAIN Kerinci. From the results of the F test, the significance value obtained from the F test for variable Y was 0.000 < 0.05, and the Fcount and Ftable values ​​were 14,180 > 3.12. From the results of the R Square test, the coefficient of determination was obtained, namely 0.269, which means that the independent variables, namely financial literacy and religiosity, were influenced by the dependent variable, namely the consumptive behavior of sharia economics students at IAIN Kerinci, amounting to 0.269 or 26.9%. The remainder was 0.741 or 74.1%. which is influenced by other variables not examined in this research.